The effect of parental regulatory focus on the loneliness stigma of college children - Zhiguang Fan; Xiaoli Shi; Wei Zhang; Bin Zhang (BMC, 2024)
Abstract Background The present study aimed to examine the relationship between regulatory focus and loneliness stigma, as well as the intergenerational transmission of the two. Specifically, the study analyzed the effects of fathers' and mothers' regulatory focus on their own and their spouses' stigma of loneliness. In addition, a mediation model was constructed to explore how parents' regulatory focus influences their children's stigma of loneliness and the potential mediating mechanisms involved. Methods Questionnaires were distributed to 470 college students and their parents, employing the Regulatory Focus Questionnaire (RFQ) and the Stigma of Loneliness Scale (SLS) to collect data. Results The analysis of intergenerational transmission effects revealed that parents' regulatory focus and loneliness stigma significantly and positively predicted children's regulatory focus and loneliness stigma, respectively. The Actor-Partner Interdependence Model (APIM) elucidated that both fathers' and mothers' promotion focus exerted significant influence on both actor and partner's loneliness stigma. Furthermore, the mediation model analysis indicated that parents' loneliness stigma, along with children's regulatory focus operate as mediators in the influence of parental regulatory focus on loneliness stigma of their college-aged offspring. Conclusions From a familial context, this study, investigated the association between regulatory focus and loneliness stigma, along with the mediating roles within parent-child groups and couples. The findings enhanced our comprehension of the interrelation between regulatory focus and loneliness stigma, underpinned by empirical evidence.